Social protection in West Africa: The status quo, lessons from other regions, implications for research - Hoddinott, John F.; Devereux, Stephen; White, Philip; Klasen, Stephan; Woolard, Ingrid; Alderman, Harold; Badiane, Ousmane; Ulimwengu, John M.; Wouterse, Fleur Stephanie (International Food Policy Research Institute, 2012)
Demand for social protection programs within more empowered segments of the poor population in African societies will be on the rise due to the historically high levels of poverty, faster economic growth, rapid urbanization, and increasingly open, pluralistic political systems. Resources required to meet this future demand will be substantial and are bound to compete with investments required to accelerate and broaden the current economic recovery process. But countries that fail to address the demand are likely to face social as well as political unrest.